Perhitungan Jumlah Eksponen Relasi Picture Pada Barisan Generator Modul Homotopi Pada Presentasi Grup 〈x,y |xyx=yxy〉 KE 〈a,b |a^2,b^3 〉 - Dedi Mardianto Mardianto (LPPM Universitas Dharma Andalas, 2022)
This paper discuss about the number of exponents relation for generator of second homotopy module for two group presentation to . From group presentation we get picture can be operation picture so that we get picture for From sequence generators we can get number of exponents relation is 0,1,2,3.